(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Intensification of agricultural land use coupled with cultivation of modern varieties has remarkably increased in Bangladesh. This in turn has resulted in deterioration of soil fertility, with emergence of macro- and micro-nutrient deficiency of crops. With this point in view, a study was undertaken to evaluate the effect of different micronutrients on crop yield, and to determine the requirement of selected micronutrients for crops and cropping patterns in the Tista Meander Floodplain (AEZ 3). Experiments were conducted at BINA substation and farmers’ fields of Rangpur district within AEZ 3. In experiment 1, the field trials were done with six micronutrients (B, Zn, Cu, Mn, Fe & Mo) designed in an additive manner. These elements were imposed to the first crop and their residual effects were monitored on the next two crops over the patterns: wheat-mungbean-T. aman. The rates of micronutrient application were 3 kg Zn, 2 kg B, 2 kg Cu, 3 kg Mn, 5 kg Fe and 1 kg Mo per hectare, added as fertilizers such as ZnSO4.7H2O, H3BO3, CuSO4.5H2O, MnCl2, FeSO4.7H2O and Na2MoO4, respectively. Other nutrients viz. N, P, K & S were applied at recommended rates to all plots; rationale was followed for the second and third crops. Intercultural operations were done whenever required. The results revealed that across the experimental sites, the crops were quite responsive to the added Zn and B. Positive effect of Cu was also noted in some cases. In the following year (expt. 2), two micronutrients, Zn and B were taken into the same cropping pattern and designed in a way to determine whether 1stcrop, 2ndcrop or 3rdcrop application is necessary to achieve satisfactory crop yield. The rates of Zn application were 0, 2, 4 & 6 kg ha–1, and the rates for B were 0, 1.5 and 3 kg ha–1. The results show that Zn application at 4 kg ha–1 coupled with B application at 1.5 kg ha–1 to the first crop can meet their requirement for the subsequent two crops in a pattern. The present study suggests that cropping pattern based field trials with Zn, B and Cu need to be done at farm level in the high cropping intensity areas of this country in order to determine micronutrient requirement of crops J. Bangladesh Agril. Univ. 15(2): 140-147, December 2017